2022
DOI: 10.1103/physrevaccelbeams.25.084001
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional emittance measurements of ultrafast electron diffraction optics corrected up to sextupole order

Abstract: Ultrafast electron diffraction (UED) is a technique in which short-pulse electron beams can probe the femtosecond-scale evolution of atomic structure in matter driven far from equilibrium. As an accelerator physics challenge, UED imposes stringent constraints on the brightness of the probe electron beam. The low normalized emittance employed in UED, often at the 10 nm scale and below, is particularly sensitive to both applied field aberrations and space charge effects. The role of aberrations is increasingly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…High quantum efficiency (QE) and low-emittance electron beams provided by multi-alkali photocathodes make them of great interest for next-generation high-brightness photoinjectors. When operated with photon energy close to their workfunction, these photocathodes can provide electron beams suitable for ultrafast electron diffraction (UED) and/or ultrafast electron microscopy (UEM) by having a lower emittance and higher QEs compared to those of metals [41,42].…”
Section: Critial Components 231 Photocathode Electron Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…High quantum efficiency (QE) and low-emittance electron beams provided by multi-alkali photocathodes make them of great interest for next-generation high-brightness photoinjectors. When operated with photon energy close to their workfunction, these photocathodes can provide electron beams suitable for ultrafast electron diffraction (UED) and/or ultrafast electron microscopy (UEM) by having a lower emittance and higher QEs compared to those of metals [41,42].…”
Section: Critial Components 231 Photocathode Electron Sourcementioning
confidence: 99%
“…Even with a state-of-the art photoemission MTE of 35 meV as demonstrated in alkali antimonide photocathodes [41,42], 10 pm normalized source emittance requires an RMS emission size of 20 nm. However, due to the proximity of the optical diffraction limit, generating laser spots of even a few microns is a non-trivial task: photocathodes in most photoinjectors are typically operated in reflection mode in high electric fields of highvoltage DC or RF guns, and the final lens of the optical imaging system for the laser to the photocathode surface cannot be located closer than tens of centimeters from the cathode surface itself, which typically yields photoemission source sizes >10 µm in RMS.…”
Section: Critial Components 231 Photocathode Electron Sourcementioning
confidence: 99%
“…Tomographic measurement techniques are used in accelerators to determine the density distribution of beam particles in phase space ρ(x, p x , y, p y , z, p z ) from limited measurements [12,13,14,15,16,17]. While these methods have been shown to effectively reconstruct 2D phase spaces from image projections using algebraic methods, application to higher-dimensional spaces requires independence assumptions between the phase spaces of principal coordinate axes (x, y, z), complicated phase space rotation procedures [18], or measurement of multiple 2D sub-spaces with specialized diagnostic hardware [19].…”
Section: Phase Space Reconstructionmentioning
confidence: 99%
“… 20,21 After the sample, preliminary experiments have shown that the use of a magnetic lens can improve the reciprocal space resolution. 22,23 However, most beamlines still utilize a propagation drift to convert the scattering angles into a spatial offset at the detector.…”
Section: Introductionmentioning
confidence: 99%